Genetic parameters in female reproductive traits of Nile tilapia (Oreochromis niloticus) - Yoshida, Grazyella Massako [UNESP]; De Oliveira, Carlos A. L.; Kunita, Natalí M.; Rizzato, Gabriel S.; Ribeiro, Ricardo P. (FapUNIFESP (SciELO), 2017)
Genetic parameters for reproductive traits in female Nile tilapia were estimated in this study using Bayesian inference method. The data set presented information from 451 Nile tilapia females that were evaluated at two different places in Maringá-Paraná-Brazil (hapas of 1 and 10 m3) and at one location in Alfenas-Minas Gerais-Brazil. A spawning examination was conducted once a week from October 2012 to March 2013 for a total of 23 weeks of evaluation. Single-trait analyses for spawning success, multiple spawning, spawning frequency, and volume of eggs/female were performed by using the software MTGSAM Threshold. The heritability estimates were 0.14, 0.16, 0.53, and 0.08 for spawning success, multiple spawning, spawning frequency and volume of eggs/female, respectively, indicating it is possible to achieve a substantial genetic gain using these reproductive traits as selection criteria.
Keywords: Bayesian Inference; Heritability; Oreochromis niloticus; Repeatability; Spawning